PELATIHAN PENGGUNAAN APLIKASI CANVA KEPADA PELAKU USAHA UNTUK MEMBUAT POSTER PROMOSI DI KECAMATAN KEDUNG WARINGIN - Zed, Etty Zuliawati; Amanda, Dea Putri; Putri, Delia; Ajiz, Sigit Abdul (Cahaya Ilmu Bangsa, 2024)
The broad impact of the advancement of the digital world on various aspects of people’s lives, including in the business sector, is very much felt. Now, everything that used to be routinely done in the real world has metamorphosed into being online-based. For small and medium traders (MSMEs) in the sub-district. Many people still do not realize the importance of graphic design and product marketing using applications that are currently popular. As a result, training on the use of the Canva Application for Graphic Design and Product Presentation will be held as part of this Community Service activity at MSMEs in Kedung Waringin Sub-district. Before the training began, observations and interviews were conducted to determine the needs of MSME traders. After that, socialization about the activities to be carried out and the training date were set. Increasing knowledge about online learning media, increasing the desire to use online learning media, and increasing the creativity and abilities of MSMEs are indicators of the success of this training. The result of this activity is an evaluation of training on the use of the Canva online design application, which is given to traders participating in the training through a questionnaire. The results of the study Showed that this training can improve people’s understanding of skills, as well as increase their creativity, so that they can become more talented as entrepreneurs. It is hoped that this training will help merchants become better at using the applications that are currently in demand by customers. Dampak luasnya kemajuan dunia digital pada berbagai aspek kehidupan masyarakat, termasuk dalam sektor bisnis, sangat terasa. Sekarang, segala sesuatu yang dulunya rutin dilakukan di dunia nyata telah bermetamorfosis menjadi berbasis online. Untuk pedagang kecil dan menengah (UMKM) di kecamatan. Banyak orang masih belum menyadari pentingnya desain grafis dan pemasaran produk menggunakan aplikasi yang sedang populer saat ini. Akibatnya, pelatihan tentang pemanfaatan Aplikasi Canva untuk Desain Grafis dan Presentasi Produk akan diadakan dalam rangka kegiatan Pengabdian Masyarakat ini di UMKM di Kecamatan Kedung Waringin. Sebelum pelatihan dimulai, observasi dan wawancara dilakukan untuk mengetahui kebutuhan pedagang UMKM. Setelah itu, sosialisasi tentang kegiatan yang akan dilakukan dan tanggal pelatihan ditetapkan. Peningkatan pengetahuan tentang media pembelajaran online, peningkatan keinginan untuk menggunakan media pembelajaran online, dan peningkatan kreativitas dan kemampuan UMKM adalah indikator keberhasilan dari pelatihan ini. Hasil penelitian menunjukkan bahwa pelatihan ini dapat meningkatkan pemahaman orang tentang keterampilan, serta meningkatkan kreativitas mereka, sehingga mereka dapat menjadi lebih berbakat sebagai pengusaha. Diharapkan bahwa pelatihan ini akan membantu pedagang menjadi lebih baik dalam menggunakan aplikasi yang sedang diminati oleh pelanggan saat ini.